Pembuatan Sediaan Gel Dari Ekstrak Herba Pegagan (Centella Asiatica L. Urban) Sebagai Obat Luka Sayat - Pratiwi Dyah Indriyani; Tyas Prasetyaningrum; Lisa Adhani (PendIPA Journal of Science Education, 2023)
Gotu kola (Centella asiatica L. Urban) contains the active ingredient saponin, an asiaticoside compound that acts as an antibiotic and spurs the production of collagen I, a protein that accelerates the wound healing process. The purpose of this study was to formulate a gel material from ethanol extract of gotu kola herb that meets the requirements of a good gel. In this study, gotu kola saponins were obtained from the extraction process carried out using a stirred extractor at 65Â°C, 350 rpm and 30, 60, 90, 120, and 150 minutes. Identification of saponins was done using FTIR (Fourier Transform InfraRed). The gel formulation was made with concentrations of 5%, 10%, and 15%. A mass transfer coefficient of 0.01240 min-1 was obtained. The IR spectrum results showed the presence of O-H groups, C-H alkane groups (CH2, CH3), C=O carbonyl groups and C-O ester groups. The results of the evaluation carried out with the three gel concentrations in the organoleptic test, pH test, viscosity test, stability test, adhesion test and spread ability test met the requirements of a good gel.